2010
DOI: 10.1016/j.jbiotec.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and hepatic differentiation of rat multipotent adult progenitor cells in microcarrier suspension culture

Abstract: Many potential applications of stem cells require large quantities of cells, especially those involving large organs such as the liver. For such applications, a scalable reactor system is desirable to ensure a reliable supply of sufficient quantities of differentiation competent or differentiated cells. We employed a microcarrier culture system for the expansion of undifferentiated rat multipotent adult progenitor cells (rMAPC) as well as for directed differentiation of these cells to hepatocyte-like cells. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…HeLa cells were inoculated at 2×10 5 cells/mL on Day 0. The procedure for microcarrier culture has been described previously [60]. On Day 5, cells on microcarriers were washed and re-suspended at 1×10 5 cells/mL in DMEM medium containing either 0.6 mM (LG) or 25 mM (HG) of glucose.…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cells were inoculated at 2×10 5 cells/mL on Day 0. The procedure for microcarrier culture has been described previously [60]. On Day 5, cells on microcarriers were washed and re-suspended at 1×10 5 cells/mL in DMEM medium containing either 0.6 mM (LG) or 25 mM (HG) of glucose.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 They also have high levels of the Oct4 transcription factor, a high growth rate, and are able to be grown as 3D aggregates. 16,17 MAPCs are also capable of forming the three germ lineages, including the mesoderm that gives rise to bone tissue when dexamethasone is supplemented. 18,19 Recent studies demonstrate that clinical grade human MAPCs (Multistem Ò ) offer clinical relevance for the treatment of autoimmune disorders and cardiac infarction (ClinicalTrials.gov NCT00677859, NCT00677222); however, no in vivo applicability studies for bone regeneration have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Any clinical cellular therapy or bioartificial liver applications will likely employ at least 5–10% of that cell number in order to to provide sufficient functional activities, or to shorten the time frame of regeneration. With a typical bioreactor, cultivating cells as aggregates [85] or on microcarriers [86], a cell concentration of at least 10 9 cell/L is easily achievable. Assuming a manufacturing process of preparing 100 doses per batch, the size of the reactor is in the range of 1000 L. Reactors with thousands of liters in volume are commonly seen in the production of viral vaccines and protein biologics [87].…”
Section: From Stem Cell Science To Technologymentioning
confidence: 99%